Optogenetics: Background, Methodological Advances and Potential Applications for Cardiovascular Research and Medicine - Joshi, Jyotsna; Rubart, Michael; Zhu, Wuqiang (Frontiers in Bioengineering and Biotechnology, 2020)
Optogenetics is an elegant approach of precisely controlling and monitoring the biological functions of a cell, group of cells, tissues or organs with high temporal and spatial resolution by using optical system and genetic engineering technologies. The field evolved with the need to precisely control neurons and decipher neural circuity and has made great accomplishments in neuroscience. It also evolved in cardiovascular research almost a decade ago and has made considerable progress in both in vitro and in vivo animal studies. Thus, this review is written with an objective to provide information on the evolution, background, methodical advances, and potential scope of the field for cardiovascular research and medicine. We begin with a review of literatures on optogenetic proteins related to their origin, structure, types, mechanism of action, methods to improve their performance, and the delivery vehicles and methods to express such proteins on target cells and tissues for cardiovascular research. Next, we reviewed historical and recent literatures to demonstrate the scope of optogenetics for cardiovascular research and medicine, such as for monitoring cardiac physiological functions, pacing of in vivo hearts and manipulating cardiac heart functions. We also examined that such optogenetic modality is vital in mimicking heart diseases, understanding the mechanisms of disease progression and also in introducing novel therapies to treat cardiac abnormalities, such as arrhythmias. We also reviewed optogenetics as a promising tool in providing high-throughput data for cardiotoxicity screening in drug development. Finally, we put forth considerations on the need of scaling up of the optogenetic system, clinically relevant in vivo and in silico models, light attenuation issues, and concerns over the level, immune reactions, toxicity, and ectopic expression with opsin expression. Detailed investigations on such considerations would accelerate the translation of cardiac optogenetics from present in vitro and in vivo animal studies to clinical therapies.